Early Embryonic Loss Following Intravaginal Zika Virus Challenge in Rhesus Macaques - Newman, Christina M.; Tarantal, Alice F.; Martinez, Michele L.; Simmons, Heather A.; Morgan, Terry K.; Zeng, Xiankun; Rosinski, Jenna R.; Bliss, Mason I.; Bohm, Ellie K.; Dudley, Dawn M.; Aliota, Matthew T.; Friedrich, Thomas C.; et al. (Frontiers in Immunology, 2021)
Zika virus (ZIKV) is an arthropod-borne virus (arbovirus) and is primarily transmitted by Aedes species mosquitoes; however, ZIKV can also be sexually transmitted. During the initial epidemic and in places where ZIKV is now considered endemic, it is difficult to disentangle the risks and contributions of sexual versus vector-borne transmission to adverse pregnancy outcomes. To examine the potential impact of sexual transmission of ZIKV on pregnancy outcome, we challenged three rhesus macaques (Macaca mulatta) three times intravaginally with 1 x 10^7 PFU of a low passage, African lineage ZIKV isolate (ZIKV-DAK) in the first trimester ( approx. 30 days gestational age). Samples were collected from all animals initially on days 3 through 10 post challenge, followed by twice, and then once weekly sample collection; ultrasound examinations were performed every 3-4 days then weekly as pregnancies progressed. All three dams had ZIKV RNA detectable in plasma on day 3 post-ZIKV challenge. At approximately 45 days gestation (17-18 days post-challenge), two of the three dams were found to have nonviable embryos by ultrasound. Viral RNA was detected in recovered tissues and at the maternal-fetal interface (MFI) in both cases. The remaining viable pregnancy proceeded to near term (approx. 155 days gestational age) and ZIKV RNA was detected at the MFI but not in fetal tissues. These results suggest that sexual transmission of ZIKV may represent an underappreciated risk of pregnancy loss during early gestation.